Feasibility analysis of automated cleaning in biopharmaceutical production using cleaning-in-place concepts from food production - Groten, Ferdinand; Henze, Chris; Joppa, Matthias; Herbst, Laura; Nießing, Bastian; Mauermann, Marc; Schmitt, Robert H. (Frontiers in Medical Technology, 2025)
In biopharmaceutical production involving cells, cell-derived products, or tissues, the cleaning of surfaces that come into direct or indirect contact with the product is currently performed mostly by hand as the initial step in decontamination. This manual approach leads to production inefficiencies, reduced reproducibility of decontamination processes, and product losses. In food production, automated processes are preferred for the decontamination of interior product contact surfaces. This article studies the feasibility of adapting the automated cleaning-in-place concepts used in the food industry to biopharmaceutical production. The focus is on spray cleaning processes and validation by cleaning simulation. An existing automated cell production platform is used as a case study for validation. The results indicate that modifying an existing platform to support cleaning-in-place presents significant challenges. However, the article outlines general design guidelines for developing new biopharmaceutical production platforms that can accommodate automated cleaning.